Magnetic Property and Therapeutic Effect of a New Co(II) Complex on Liver Cancer by Regulating the Expression of miRNA31 - Zhenshan Guo; Jun Zhen; Zhoujia Yao; Yemeng Wang; Chenlu Jin (International Journal of Polymer Science)
Employing the flexible hexacarboxylate ligand of 1,3,5-triazine-2,4,6-triamine hexaacetic acid (H6TTHA) to assemble with Co(NO3)2·6H2O, we have acquired a novel coordination compound, i.e., [Co2(H2TTHA)(H2O)]n·6n(H2O) (1). The analysis of single X-ray diffraction indicated that the H2TTHA2- ligand μ5-bridges connected the Co(II) ions into a two-dimensional layered architecture. Moreover, the magnetic property of 1 was also investigated between 2 and 300 K under 1000 Oe applied magnetic field. The novel compound’s inhibitory activity against the viability of cancer cell was determined through CCK-8 assay, and the expression of miRNA31 in liver cancer cells was detected via the real-time RT-PCR.